COMPARISON OF COMMA INCISION VERSUS MODIFIED WARD'S INCISION IN MANDIBULAR THIRD MOLAR SURGERY- A CLINICAL STUDY - Lohana, Vishal; Sundas Kunbher,; Shumaila Younus,; Suneel Kumar Punjabi,; Omaiz Memon,; Ghulam Ali, (Journal of Ayub Medical College Abbottabad, 2024)
Background: To evaluate the effectiveness of the two flap/incision techniques, viz. the comma incision versus modified ward's incision in mandibular third molar surgery. Methods: This randomized research comprised of 126 participants, 63 in every group. Male and female patients between the ages of 20 and 45 who had mesio-angular impacted mandibular third molar till the age of 20 to 24 years were enrolled in the research. Patients with specific problems, that is pregnancy, trismus, pericoronitis, horizontally impacted wisdom teeth, and disto-angular impaction, and limited mouth opening in which there was difficulty in access to third molar region due to any reason were omitted from the study. The independent t-test were used to evaluate the mouth opening over groups, and the chi-square test were used to evaluate the pain and edema. Results: The participants average age was 31.16±9.29 years. On the first day, the comma shaped group reported significantly mild pain (47.6%) compared to the Modified Ward's group (30.2%) (p=0.230). On the seventh day, the comma shaped group reported significantly greater mild pain (63.5%) and decreased severe pain (1.6%) compared to the Modified Ward's group, which reported decrease mild pain (55.6%) and more severe pain (4.8%) (p=0.032). On the first, third and seventh days, mouth opening was also considerably higher in the comma-shaped group than in the Modified Ward's group. On the third and seventh days, swelling was much decreased in the comma-shaped group than in the Modified Ward's group. Conclusion: Our study delivers some proofs that the comma-shaped incision is more effective than the modified Widman's incision at promoting good mouth opening and decrease post-operative edema and discomfort after flap surgery.